2020
DOI: 10.1039/d0ra06107g
|View full text |Cite
|
Sign up to set email alerts
|

Hyper oxygen incorporation in CeF3: a new intermediate-band photocatalyst for antibiotic degradation under visible/NIR light

Abstract: Hyper doping O acts as a nonradiative center and generates an intermediate band with F atoms, exhibiting efficient photocatalysis activities under visible/NIR light.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…In addition, there is a weak satellite peak at a higher binding energy, which is in good agreement with the previous studies of CeF 3 thin films. [23,24] The F to Ce atom ratio extracted from the core-level peak areas confirms that the obtained thin film is stoichiometric CeF 3 .…”
Section: Resultssupporting
confidence: 60%
“…In addition, there is a weak satellite peak at a higher binding energy, which is in good agreement with the previous studies of CeF 3 thin films. [23,24] The F to Ce atom ratio extracted from the core-level peak areas confirms that the obtained thin film is stoichiometric CeF 3 .…”
Section: Resultssupporting
confidence: 60%
“…The results also imply that narrow sub-bandgaps can be achieved in doped ceramics and favour multiphoton absorption or accumulation of electrons for boosting solar energy conversion. 41 demonstrated that the interband transitions of three absorption peaks were derived from Ni 3d x 2 Ày 2/ Ni 3d z 2/Ni 3d xy transitions. When the photon energy reaches $1.4 eV, the electrons can be excited from the VBM to Ni 3d z 2.…”
Section: Resultsmentioning
confidence: 93%
“…The results also imply that narrow sub-bandgaps can be achieved in doped ceramics and favour multiphoton absorption or accumulation of electrons for boosting solar energy conversion. 41 Hence, the excellent visible-light PHE rate in the La/Ni-modified KN system can be ascribed to sub-bandgap formation and strong visible/NIR absorption.…”
Section: Resultsmentioning
confidence: 98%
“…To address the challenge mentioned above, nonmetallic ion doping in CeF 3 is focused on further developing an appropriate visible light responding photocatalyst. On the other hand, our group has reported an oxygen-rich doped CeF 3 exhibiting a suitable electronic structure on visible light photocatalysis in contrast to the intrinsic electronic structure . In this paper, O,N-codoped CeF 3 nanoparticles are synthesized by the hydrothermal method at a variety of temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, our group has reported an oxygen-rich doped CeF 3 exhibiting a suitable electronic structure on visible light photocatalysis in contrast to the intrinsic electronic structure. 23 potentials, both of which profoundly influence their photocatalysis properties.…”
Section: Introductionmentioning
confidence: 99%